Estrategias de gestión escolar para la promoción de proyectos de apoyo a la comunidad en la escuela de educación básica Rafael Quevedo, del barrio Mollepamba , cantón Saquisili , en el año 2014-2015 - Quishpe Olmos, Gloria Liliana (2016)
This thesis research was carried out in order to understand and implement different strategies School Management at the School of Basic Education Rafael Quevedo, high school and turn give educational actors guidelines for the proper use of new strategies and integration of the educational community. The educational process in today's society has registered great changes in recent years a challenge for teachers, which is why we have proposed to the school to be taken as a fundamental role in education. The school management is the process by which it is directed, leads, directs and administers an educational institution, problems are recognized and solutions are proposed and so thereby achieve in students, teachers, and parents teamwork and therefore education where they can develop skills for quality education.